HO2 reaction kinetics in an atmospheric pressure plasma jet determined by cavity ring-down spectroscopy. (25th September 2018) - Gianella, M; Reuter, S; Press, S A; Schmidt-Bleker, A; Helden, J H van; Ritchie, G A D
Abstract: Hydroperoxyl ( HO 2 ) is detected in the effluent of an atmospheric pressure plasma jet (PJ) by cavity ring-down absorption spectroscopy. Laser radiation at 1506.4 nm is used to determine HO 2 concentrations directly in the plasma effluent at atmospheric pressure as well as indirectly after sampling through a pinhole and expanding to 5.33 kPa . To unravel the HO 2 reaction kinetics, the argon feed gas is humidified and the PJ is equipped with a gas curtain device that controls the surrounding atmosphere. Varying the curtain gas composition from pure nitrogen to pure oxygen leads to a five to six-fold increase in HO 2 concentrations towards higher oxygen concentrations. A reaction kinetics model considering near-field and far-field reactions describes the reaction pathways that determine the hydroperoxyl concentration and is in good agreement with the measurements at both low and atmospheric pressure.